A loss-free multipathing solution for data center network using software-defined networking approach - Fang, Shuo (2013)
Conventional Ethernet protocols struggle to meet the scalability and performance requirements of data centers. Viable replacements have been proposed for data center ethernet (DCE): link-layer Multipathing (MP) is deployed to replace spanning tree protocol (STP) and thus improve network throughput; end-to-end link-layer congestion control (CC) is proposed to better guarantee loss-free frame delivery for Ethernet. However, little work has been done to incorporate MP and CC to offer a more comprehensive solution for DCE. In this paper, we propose a two-tier solution by integrating our dynamic load balancing Multipath (DLBMP) scheme with CC. Instead of using two separate parameters, i.e., path load and buffer level, to trigger MP and CC, our solution only needs to monitor path load metric to manage MP and CC in an integrated way. Different from a single CC mechanism, which generates congestion notifications from network core, our integrated CC can make use of link load information in access switches which directly inform sources to control their traffic admission. To minimize overhead and accelerate update, SDN techniques are employed in our implementation, which decouples routing intelligence from data transmission. Hence, data sources can react more rapidly to congestion and network can be guaranteed with loss-free delivery. In addition, our MP scheme is further improved by introducing application-layer flow differentiation. With such a fine flow differentiation (FFD) mechanism, traffic can be more evenly distributed along multipaths, resulting in better bandwidth utilization. Simulation results show that our combined solution can further improve network throughput with FFD mechanism and guarantee loss-free delivery with integrated CC.